Effects of Place-Based Learning Strategy on Social Studies Pre-Service Teachers’ Environmental Knowledge, Attitudes and Responsible Behaviour in Colleges of Education, South-West, Nigeria - ADEYEMI, Babatunde Adeniyi; OLAPADE, Christopher Bola (Ilorin Journal of Education, 2023)
In teaching Environmental Education in Social Studies, several strategies have been used without appreciable results; Therefore, this study investigated the effects of Place-based instructional strategy on Social Studies pre-service teachers' environmental knowledge, attitudes and responsible behaviour in Colleges of Education, South-west, Nigeria. The study adopted the pre-test, post-test, control group quasi-experimental design. The target population was 200 level pre-service teachers in Colleges of Education in South-west Nigeria. The sample consisted of 360 (180 males and 180 females) students, selected using stratified random sampling techniques. Three instruments namely: Knowledge of Environmental Concepts (KECT) (r=0.88); Environmental attitude Scale (EAS) (r=0.81); Environmental Responsible Behaviour Scale (ERBS) (r=0.76), were used to gather data. The data were analysed using frequency counts, percentages and Multivariate Analysis of Covariance (MANCOVA). Results showed that there was a significant main effect of treatment (F(6,704) =11,000,p<.05); while there was no significant effect of gender on the dependent variables (F(3,353)=1,710, p>.05). However, there was a significant interaction effect of treatment and gender, (F(3,231) = 3,575, p<.05); In conclusion, the place-based learning strategy have proved to be more effective than the conventional lecture strategy at improving students' knowledge, attitudes and behaviour to environmental issues and concepts in Social Studies. Therefore, it is recommended that teachers at all levels should adopt this strategy in their classroom teaching of environmental concepts in the Social Studies curriculum.